Ladoni - Aristakisi͡an, Artur, 1961-; Ḳaplan, Naḥum, 1811-1879 (VGIK, 1994)
Although the film documents the street life in the former Soviet city of Kishinev, it is more of an exploration of space, proximity and systems. Includes footage of beggars, fanatics, street crazies, rag-pickers, homeless children, elderly Jews and gypsies. The film features a narration by the director, who is addressing his unborn son.